PENGARUH MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLECTING, EXTENDING (CORE) TERHADAP KEMAMPUAN BERPIKIR KRITIS - Kemala Putri Hadiyati; Purwati Kuswarini Suprapto; Popo Musthofa Kamil (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2019)
The study aims to determine the effect of Connecting, Organizing, Reflecting, Extending (CORE) learning model toward criticial thinking skill of students on the senses system material. This research was conducted from September 2018 to June 2019. The research method used is true experiment. Population in this research is all 11th grade Mathematics and Science of State Senior High School at Tasikmalaya. Sample of this research is 2 classes the 11th grade Mathematics and Science, taken by cluster random sampling technique. The result of the research data were analyzed using the ANCOVA test. Based on the result of the research that there was an influence of the Connecting Organizing Reflecting Extending (CORE) learning model toward criticial thinking skill of students on the senses system material in the 11th grade Mathematics and Science of State Senior High School at Tasikmalaya.Keyword:CORE, criticial thinking, sense system